High Summer Temperatures Take a Toll on Trees - Guha, Anirban; Vincent, Christopher (EDIS, 2022)
A quick body temperature test is common these days before entering many workplaces, hospitals and clinics due to the ongoing COVID-19 pandemic. The purpose is to screen people for fevers, usually with a non-contact infrared thermometer. Measurement of plant body temperatures also has become common for many field crops, not to screen for infectious diseases, but to assess seasonal heat impacts on plants. This article describes a new understanding of how citrus trees respond to high leaf temperatures, and what growers can do about it.